Substrate signal inhibition in Raman analysis of microplastic particles - Elsayed, Ahmed A. (2023)
In Raman analysis, the substrate material serves very often for signal enhancement, especially when metallic surfaces are involved; however, in other cases, the substrate has an opposite effect as it is the source of a parasitic signal preventing the observation of the sample material of interest. This is particularly true with the advent of microfluidic devices involving either silicon or polymer surfaces. On the other hand, in a vast majority of Raman experiments, the analysis is made on a horizontal support holding the sample of interest. In our paper, we report that a simple tilting of the supporting substrate, in this case, silicon, can drastically decrease and eventually inhibit the Raman signal of the substrate material, leading to an easier observation of the target analyte of the sample, in this case, microplastic particles. This effect is very pronounced especially when looking for tiny particles. Explanation of this trend is provided thanks to a supporting experiment and further numerical simulations that suggest that the lensing effect of the particles plays an important role. These findings may be useful for Raman analysis of other microscale particles having curved shapes, including biological cells.